2009
DOI: 10.1080/14647270802621358
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and its soluble receptor in patients with polycystic ovary syndrome undergoing IVF

Abstract: We aimed to examine the behaviour of the angiogenetic factor vascular endothelial growth factor (VEGF) and its soluble receptor (sVEGFR-1) in polycystic ovary patients undergoing In vitro fertilisation (IVF) compared with respect to normally ovulating controls. Levels of VEGF and sVEGFR-1 were compared in follicular fluid and serum, both on the day of human choriogonadotropin (hCG) administration and on the day of oocyte retrieval (OR), in controls and polycystic ovarian syndrome (PCOS) patients undergoing IVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 22 publications
1
45
3
Order By: Relevance
“…Our finding is in disagreement with Agrawal et al (2002 (4) , Artini et al (2006) (20) , Artini et al (2009) (21) and Mary et al (2016) (22) who found elevated levels of VEGF in serum and follicular fluid of patients with PCOS undergoing IVF. The increased levels of VEGF explained by the finding that the release of VEGF by granulosa lutein cells is augmented by insulin (4,23) and that luteinized granulose cells in women with PCOS are more sensitive to insulin (23) .…”
Section: Discussion:-contrasting
confidence: 57%
“…Our finding is in disagreement with Agrawal et al (2002 (4) , Artini et al (2006) (20) , Artini et al (2009) (21) and Mary et al (2016) (22) who found elevated levels of VEGF in serum and follicular fluid of patients with PCOS undergoing IVF. The increased levels of VEGF explained by the finding that the release of VEGF by granulosa lutein cells is augmented by insulin (4,23) and that luteinized granulose cells in women with PCOS are more sensitive to insulin (23) .…”
Section: Discussion:-contrasting
confidence: 57%
“…VEGF has been shown to be increased in ovarian tissue [11, 12] as well as serum and follicular fluid [5, 1315] of PCOS women compared with non-PCOS controls. In addition, sFlt-1, the soluble receptor for VEGF and PlGF, has been reported to be decreased in serum and follicular fluid of PCOS women undergoing controlled ovarian stimulation, contributing to increased VEGF bioavailability [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sFlt-1, the soluble receptor for VEGF and PlGF, has been reported to be decreased in serum and follicular fluid of PCOS women undergoing controlled ovarian stimulation, contributing to increased VEGF bioavailability [15]. The increased serum VEGF levels in PCOS were shown to correlate with increased ovarian vascularity in these women [13, 18], while laparoscopic ovarian drilling has been shown to reduce Doppler indices of ovarian stromal blood flow [24] with a concomitant reduction in circulating VEGF levels [25], supporting the notion that VEGF contributes to the vascular changes observed in PCO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased follicular fluid VEGF levels in PCOS were found to be closely correlated with the development of OHSS, and high VEGF levels were shown to indicate immature oocyte and disordered fertilization (75). However the opposite results were obtained in another study, and increased follicular fluid VEGF was determined to affect the oocyte quality positively, and to increase retrieval of the MII oocytes (76). A study group demonstrated increased follicular fluid VEGF in the ovaries exposed to prolonged hCG effect in the PCOS patients, and they also showed increased oocyte and embryonic qualities and improved fertilization rates (77); after a couple of years, the same group showed decrease of VEGF and E2 levels in the follicular fluid in the PCOS cases following the administration of GnRH antagonist, and they determined that this resulted in disordered follicular development, and decreased oocyte and embryonic qualities, compared to the agonist-administered cycles (78).…”
Section: Introductionmentioning
confidence: 74%